'An Old Carriage with New Horses': Nietzsche's Critique of Democracy. Issue 8 (16th November 2016) - Drochon, Hugo
SUMMARY: Debates about Nietzsche's political thought today revolve around his role in contemporary democratic theory: is he a thinker to be mined for stimulating resources in view of refounding democratic legitimacy on a radicalised, postmodern and agonistic footing, or is he the modern arch-critic of democracy budding democrats must hone their arguments against? Moving away from this dichotomy, this article asks first and foremost what democracy meant for Nietzsche in late nineteenth-century Germany, and on that basis what we might learn from him now. To do so, it will pay particular attention to the political, intellectual and cultural contexts within which Nietzsche's thought evolved, namely Bismarck's relationship to the new German Reichstag, the philological discovery of an original Aryan race, and Nietzsche's encounter with Gobineau's racist thought through his frequentation of the Wagner circle. It argues that Nietzsche's most lasting contribution to democratic thinking is not to be found in the different ways he may or may not be used to buttress certain contemporary ideological positions, but rather how his notions of 'herd morality', 'misarchism' and the genealogical method still provides us with the conceptual tools to better understand the political world we inhabit.